Influence of Job Motivation on Staff Productivity in Academic Libraries in Niger State, Nigeria - Babalola, G.A.; Oyedum, G. U.; Aboyade, W.A. (MiddleBelt Journal of Library and Information Science, 2020)
The study examined the influence of job motivation on the productivity of staff in academic libraries in Niger State. Survey research design was used to cover all the 12 academic libraries involved in the study. Non-probabilistic or purposive sampling technique was used to select four (4) out of the twelve (12) academic libraries. The four libraries were selected based on the research cum learning activities that go on in the selected institutions which would not necessitate duplication of similar institutions. Total enumeration was used and in all, 208 library personnel consisting professional, para-professional and support staff were involved. Findings of the research were analyzed in simple descriptive statistics of frequency counts and percentages. The research revealed that job motivation had strong and positive influence on the productivity of the staff. Influence of job motivation on staff productivity was felt most in Ibrahim Babangida University, Lapai with 94.7% respondents. This was closely followed by Federal College of Education, Kontagora with 92.9% respondents. Out of all the motivational items listed, money (salary) had the greatest influence on the productivity of staff in the institutions investigated for the study. It was recommended among others that the salaries and other financial allowances of the staff of the affected institutions be at par with what are obtained in similar organisations and that slashing of allowances of the staff under whatever guises should be discouraged discontinued because of its anti- productive tendencies.